The optimization of RBD palm oil epoxidation process using D-optimal design - Nurazira Mohd Nor,; Darfizzi Derawi,; Jumat Salimon, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The epoxidation process of RBD palm oil was carried out using in situ generated performic acid. The effect of various process variables such as the formic acid towards hydrogen peroxide mole ratio, the reaction temperature and the reaction time were optimized by using response surface methodology (RSM). The D-optimal design was used to evaluate the influence of process variables and their interaction in order to obtain the process optimum conditions. The results showed that the optimum conditions of the epoxidation process were at 5.91 mole ratio of formic acid towards 3.60 mole of hydrogen peroxide, reaction temperature of 40ºC and reaction time of 2.55 h. At the optimum condition, the epoxidised RBD palm oil (EPO) yield was 86% with oxirane oxygen content (OOC) of 3.46%. The results showed in good agreement with the predicted values from the RSM model.